ECONOMIC RELATIONSHIP BETWEEN TRANSPORT AND EXPORT-IMPORT OPERATIONS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Transport plays a pivotal role in the development and facilitation of international trade, particularly in export and import operations. The relationship between transport and export-import operations is deeply intertwined with global economic growth, supply chain efficiency, market accessibility, and the competitiveness of nations. Exploring this relationship reveals the critical functions transportation serves in ensuring the seamless movement of goods, reducing transaction costs, and influencing trade patterns among countries and regions.